Correlation between single crystal data and molecular mechanics calculation of 3-(2-hydroxy-phenylimino)-1,3-diphenyl-propan-1-one - Orabi, Adel Sayed; El-Sakka, Sahar Said (European Journal of Chemistry, 2019)
The Schiff base 3-(2-hydroxy-phenylimino)-1,3-diphenyl-propan-1-one (L), was prepared and characterized by elemental analysis, IR, 1H NMR and mass spectral techniques. The crystal and molecular structures were determined by using the single crystal X-ray diffraction data. The crystal was triclinic with unit-cell dimensions: a = 9.051(3) Å, b = 10.245(3) Å, c = 11.016(3) Å, α = 69.28(2)°, β = 81.66(2)°, γ = 64.25(2)°, space group is Pī and Z = 2. The structure was refined by least squares method. The single crystal was prepared by supersaturating method using tetramethoxysilane as gelling agent. Energy minimization for locating stable conformations and single point energy calculations for comparing the obtained and calculated conformations of the same molecule were carried out using molecular mechanics method (MM2 force field). The bond lengths and the bond angles were calculated and compared with the values obtained from the single crystal analysis. The obtained results were discussed and evaluated. Generally, the calculated parameters are in good agreement with the corresponding X-ray diffraction values. The obtained results reveal that, the amine-imine tautomerism is more preferable than keto-enol form and the intra-hydrogen bond stabilize the amine-imine tautomerism.